Reasoning about linkages with dynamic geometry. (March 2020) - Kovács, Zoltán; Recio, Tomás; Vélez, M. Pilar
Abstract: We illustrate an on-going work on the crossroad of mechanical linkages, dynamic geometry and automated reasoning. In particular, we exemplify how some automated reasoning tools (ART) based on symbolic computation and recently implemented in GeoGebra, can be used for linkage exploration. For instance, when considering linkages for generating specific algebraic curves, such as Peaucellier's construction of a straight line, we will show how these ART can help towards the verification (automatic proving) of the correctness of the linkage construction, as well as for finding (automatic discovery) a suitable modification on a given linkage for achieving a desired movement.